17 Challenges and implications of feeding diets with excess concentrations of leucine to growing-finishing pigs - Tokach, Mike D (J Anim Sci, 2020)
Excess dietary leucine stimulates the key enzymes involved in branched-chain catabolism causing breakdown of all branched-chain amino acids, including isoleucine and valine. Branched-chain amino acids share a common brain transporter with other large neutral amino acids (LNAA). Excess levels of one of the LNAA increases brain uptake of that amino acid and decreases the uptake of the other LNAA, including tryptophan. Thus, excess leucine can impact the requirements for many amino acids. From a practical basis, this effect was first demonstrated with diets containing blood meal, but was thought to be of limited concern unless high blood meal diets were fed. Use of corn dried distillers grains with solubles (DDGS) or high protein DDGS in corn-based diets results in diets containing excess leucine. These high leucine levels are of limited concern if adequate levels of other branched-chain amino acids and LNAA are fed, which is often the case if the diet consists largely of intact protein sources. Feed grade amino acids, such as L-lysine, L-threonine, L-tryptophan, DL-methionine, L-valine, and L-isoleucine have been widely adopted as a means to lower nitrogen excretion and diet cost. Including these amino acids in diets containing corn products reduces dietary leucine; but the resulting diets are formulated near the requirement for the first 6 limiting amino acids, including valine, isoleucine, and tryptophan, while still being high in leucine. The excess leucine increases the requirements for valine, isoleucine, and possibly other LNAA, such as tryptophan and possibly others. The exact relationship between these amino acids and how to handle them in practical diet formulation is still being elucidated; however, recent meta-analysis and experimental data confirm the importance of these ratios and provide useful direction for future research.